Smoking Cessation and Coronary Artery Calcification in CKD. Issue 6 (June 2021) - Lee, Mi Jung; Park, Jung Tak; Chang, Tae Ik; Joo, Young Su; Yoo, Tae-Hyun; Park, Sue Kyung; Chung, Wookyung; Kim, Yong-Soo; Kim, Soo Wan; Oh, Kook-Hwan; Kang, Shin-Wook; Choi, Kyu Hun; et al.
Visual Abstract: Abstract : Background and objectives: Smoking is associated with vascular calcification and a higher risk of cardiovascular disease. In this study, we investigated the association of smoking dose and cessation with coronary artery calcification (CAC) in patients with CKD. Design, setting, participants, & measurements: From a nationwide, prospective cohort of Korean patients with CKD, 1914 participants were included. Prevalent CAC was defined as an Agatston score >0, using computed tomography. CAC progression was defined as ≥30%/yr increase in Agatston score at the 4-year follow-up examination in patients with baseline CAC. Results: Prevalent CAC was observed in 952 (50%) patients. Compared with never smokers, former smokers had a similar prevalence ratio for CAC, but current smokers had a 1.25-fold higher prevalence ratio (95% confidence interval [95% CI], 1.10 to 1.42). Among former smokers, a lower smoking load of <10 pack-years (prevalence ratio, 0.77; 95% CI, 0.65 to 0.90) and longer duration of smoking cessation (prevalence ratio for 10 to <20 years, 0.85; 95% CI, 0.73 to 0.98: prevalence ratio for ≥20 years, 0.83; 95% CI, 0.73 to 0.96) were associated with lower risk of prevalent CAC compared with current smoking. The prevalence ratios did not differ between never smoking and long-term cessation. However, short-term cessation with heavy smoking load was associated with a higher risk of prevalent CAC (prevalence ratio, 1.21; 95% CI, 1.03 to 1.40) compared with never smoking. CAC progression was observed in 111 (33%) patients with baseline CAC. Compared with never smokers, former smokers showed a similar risk of CAC progression, but current smokers had a higher risk (relative risk, 1.92; 95% CI, 1.30 to 2.86). Conclusions: In CKD, former smoking with a lower smoking load and long-term cessation were associated with a lower risk of prevalent CAC than current smoking. CAC progression was more pronounced in current smokers.